Normer, intervention og kon ikt på Afrikas Horn – betydningen for Somalia - Enevig, Martin (Politik, 2013)
Inter-state con ict in Africa is rare. ough the continent has seen more than its fair share of con icts, the majority of these have been internal rather than inter-state. A notable exception is the Horn of Africa, where inter-state con ict is more common than in Africa as a whole. An important factor in explaining this is the region’s colonial history, which di ers from the general African history of colonization in that the region’s central state, Ethiopia, was never colonized. is article argues that Africa has a stronger non-intervention norm than the rest of the world, because it is underlined by a strong anti-colonialism norm. Due to Ethiopia’s special role in the region, the two norms run counter on the Horn resulting in a weaker non-intervention norm. e article analyses how the weaker non-intervention norm a ects inter-state relations on the Horn and what this means for the current political developments in Somalia.